Production Of Acid-Activated Bleaching Earth From Bentonite Clay For Edible Oil Bleaching - Tsiye Hailemariam (International Journal of Science and Environment (IJSE), 2025)
The main aim of this study was to produce acid-activated bleaching earth from bentonite clay for edible oil bleaching, which is a clay mineral that can be used in its natural or acid-activated states to clarify and reduce the colour intensity of fats and edible oil. This study was conducted in two stages. The first involved the characterization of activated bentonite clay (moisture content and bulk density determination) and choosing an effect on acid-activated bleaching earth performance by considering the significant parameters, which are sulfuric acid concentration (1, 3, 5M), bleaching time (25, 40 and 60min) and dosage of acid-activated bleaching earth per millilitre of impure edible oil (1.5, 4.5, 6g). The raw bentonite clay acquired from Afar Bentonite Mineral Mining Plc. was activated by diluted sulfuric acid at a temperature of 90℃, neutralized, and the impure edible oil was prepared. A 3M acid concentration at a bleaching time of 40 min and 4.5 g of acid-activated bleaching earth dosage resulted in the highest percentage of colour reduction, which was 97%. In general, the findings of this study support the notion that bentonite clay is an effective adsorbent for edible oil bleaching. This study has strengthened the idea that acid-activated bentonite can eliminate pigments that are the result of different impurities, while also reducing the health impact of unqualified edible oil products.